Detection of fiber-digesting bacteria in the forestomach contents of llamas (Lama glama) by PCR - Cerón Cucchi, María Esperanza (2013)
The high fibrolytic activity and large biomass of strictly-anaerobic bacteria that inhabit the rumen makes them primarily responsible for the degradation of the forage consumed by ruminants. Llamas feed mainly on low quality fibrous roughages that are digested by an active and diverse microflora. The products of this fermentation are volatile fatty acids and microbial biomass, which will be used by the animals. The aim of this study was to detect the three major fiber-digesting anaerobic bacteria in the forestomach contents of llamas by PCR. In this study, we detected Ruminococcus albus, Ruminococcus flavefaciens and Fibrobacter succinogenes in the forestomach contents of eight native llamas from Argentina.